Analysis of outcomes of robot-assisted laparoscopic pyeloplasty in children from a tertiary pediatric center in South India - Vidhya, Tamizhvanan; Rajiv, Padankatti; Sripathi, Venkat (Frontiers in Pediatrics, 2024)
AIM: To analyse the outcome of Robot Assisted Laparoscopic Pyeloplasty (RALP) in children with Pelvi Ureteric Junction Obstruction (PUJO) over a 10 period in a tertiary care center in Southern India. METHODS: This is a detailed analysis of prospectively acquired data from 2013 to 2023 of all children who underwent RALP in our institution. Pre and postoperative renal ultrasound and isotope renography were analysed. Patient demographics, time taken for the procedure, post operative pain relief, steps of the operation and post-surgery follow-up protocol have been outlined in detail. RESULT- 201 children underwent RALP, 185 children had completed at least one year of follow-up and were included for analysis. The mean age of the cohort was 4.9yrs (1mon-17yrs) of which the majority were males (77.3%). 25 children (13.5%) were <1 year of age. Left sided PUJO was more common. The mean console time was 76.5min (40-180) and average hospital stay was 2.8 days (2-5). Mean reduction in Antero-Posterior Diameter (APD) of renal pelvis post-surgery was more than 50% of preop value and statistically significant (3.3+/-0.3cm to 1.9+/-0.9cm). At the end of one year, overall reduction in renal size was also significant (9.7+/-2.3 cm preop to 8.9+/- 1.8cm post op) The pre-op SFU grade of hydronephrosis was compared to the post-op SFU grade and improvement (resolution/ downgrading) was found to be statistically significant. The median split renal function in this series was 39% preop and 43% post op and the overall functional improvement after RALP was significant. 181 children had a successful outcome (97.8%), 4children had persistent severe hydronephrosis, underwent redo stenting and/ or redopyeloplasty (2.1% failure rate). Post operative complications as per Clavien-Dindo classification were Grade 1 in 3 children and Grade 3b in 2 children. Conversions to open surgery was none in the series. CONCLUSION RALP is the minimally invasive procedure of choice for PUJO in children in our institution. It is safe with consistently excellent results and minimal complications. Our outcomes are comparable to published series. We trust that our experience will serve as a roadmap for those centers (esp in South Asia) embarking on a pediatric robotic program.